Low‐dose IL‐2 prevents murine chronic cardiac allograft rejection: Role for IL‐2‐induced T regulatory cells and exosomes with PD‐L1 and CD73. Issue 9 (9th June 2022) - Ravichandran, Ranjithkumar; Itabashi, Yoshihiro; Fleming, Timothy; Bansal, Sandhya; Bowen, Sara; Poulson, Christin; Bharat, Ankit; Bremner, Ross; Smith, Michael; Mohanakumar, Thalachallour
Abstract: To determine the effects and immunological mechanisms of low‐dose interleukin‐2 (IL‐2) in a murine model of chronic cardiac allograft rejection (BALB/c to C57BL/6) after costimulatory blockade consisting of MR1 (250 μg/ip day 0) and CTLA4‐Ig (200 μg/ip day 2), we administered low‐dose IL‐2 (2000 IU/day) starting on posttransplant day 14 for 3 weeks. T regulatory (Treg) cell infiltration of the grafts was determined by immunohistochemistry; circulating exosomes by western blot and aldehyde bead flow cytometry; antibodies to donor MHC by immunofluorescent staining of donor cells; and antibodies to cardiac self‐antigens (myosin, vimentin) by ELISA. We demonstrated that costimulation blockade after allogeneic heart transplantation induced circulating exosomes containing cardiac self‐antigens and antibodies to both donor MHC and self‐antigens, leading to chronic rejection by day 45. Treatment with low‐dose IL‐2 prolonged allograft survival (>100 days), prevented chronic rejection, and induced splenic and graft‐infiltrating CD4+ CD25+ Foxp3 Treg cells by day 45 and circulating exosomes (Foxp3+) with PD‐L1 and CD73. MicroRNA 142, associated with the TGFβ pathway, was significantly downregulated in exosomes from IL‐2‐treated mice. In conclusion, low‐dose IL‐2 delays rejection in a murine model of chronic cardiac allograft rejection and also induces graft‐infiltrating Tregs and circulating exosomes with immunoregulatory molecules. Abstract : In a murine model of cardiac allograft transplantation, low‐dose interleukin‐2 treatment attenuates chronic rejection and induces graft‐infiltrating T‐regulatory cells and circulating exosomes with immunoregulatory molecules.